Dystonic Movement Disorder as Symptom of Catatonia in Autism Spectrum Disorder - Riccio, Maria Pia; Siracusano, Rosamaria; d’Alessandro, Ilaria; Marino, Maria; Bravaccio, Carmela (Case Reports in Psychiatry, 2020)
Background. Catatonia is increasingly recognized as a comorbid psychiatric condition in autism spectrum disorder (ASD), but the overlap of behavioral characteristics between these disorders raises many diagnostic challenges. Moreover, recognizing symptoms in ASD patients with medium-low functioning might be difficult. Literature on this argument is poor, especially for children. Case presentation. We report the case of an ASD patient with low cognitive functioning, who presented a complex symptomatology, characterized by progressive regression with loss of autonomy and involuntary movements that assume “dystonic” features. Organic pathology was excluded, and catatonia, with peculiar dystonic characteristics, was diagnosed. An intervention based on elimination of stressful factors, resumption of routines, and support for parents led to the resolution of catatonic symptoms. Conclusions. The case describes the presence among the catatonic symptoms in ASD of involuntary “dystonic” movements; so far, little reported in literature; it highlights that the catatonia may present with a broad spectrum of motor abnormalities. There is still little evidence for treatment of catatonia and ASD. Our case highlights how it is equally important to take into account triggering factors when implementing a nonpharmacological treatment. So, it represents an example of diagnostic and therapeutic challenges of catatonia in ASD, especially in low functioning forms.